THE EFFECT OF EFFLURAGE MASSAGE USING VCO AND PROPER POSITIONING ON PRESSURE ULCER RISK SCORES IN BED-BOUND PATIENTS - Rosalia Ratna; Ekatrina Wijayanti; Emmelia Ratnawati (Bagian Keperawatan Fakultas Kedokteran Universitas Sriwijaya, 2026)
Aim: Pressure ulcers are one of the serious complications of bedrest patients that can cause tissue damage, increase length of stay (LOS), and worsen the overall condition of patients if optimal prevention is not carried out. The purpose of this study was to determine the effect of effleurage massage using VCO and proper positioning on the pressure ulcer risk score of bedrest patients in Inpatient Room of Hospital in Yogyakarta. Method: This study employed a quasi-experimental design with pre-test and post-test on two groups, involving 30 respondents, with 15 respondents in the intervention group and 15 respondents in the control group. The intervention group received effleurage massage using VCO and proper positioning, while the control group only received proper positioning intervention. The instrument used was the Norton Scale, which was administered on the first day (pre-test) and the third day (post-test). The Paired t-test was used to determine the Norton scores in the intervention and control groups, while the independent t-test was used to determine the difference in Norton scores between the two groups. Result: The results showed a significant decrease in pressure ulcer risk scores in the intervention group after two days of intervention, from 12.67 to 14.80 (p value 0.000). Meanwhile, the control group experienced a decrease in scores, but not as significant as in the intervention group, from 13.13 to 13.80 (p value 0.004), indicating that the combination intervention was more effective in reducing pressure ulcers. Conclusion: With a significant difference in Norton post-test scores between the two groups, and a greater increase in Norton scores in the intervention group, this shows that the combined intervention was more effective than just one intervention alone.